THE EFFECT OF FOOT MASSAGE AND PROGRESSIVE MUSCLE RELAXATION ON SLEEP QUALITY IN CONGESTIVE HEART FAILURE (CHF) PATIENTS AT GRANDMED LUBUK PAKAM HOSPITAL - Karokaro, Tati Murni; Kardina Hayati; Tania Diah Masitah (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Cardiovascular disease, also known as heart disease, generally refers to conditions involving narrowing or blockage of blood vessels that can lead to heart attack, chest pain (angina), or stroke. Other heart conditions that affect the muscles, valves, or rhythm of the heart are also considered forms of heart disease. Rest and sleep are a major part of physical and mental health. Every individual who is in the hospital will have poor quality sleep if the results are compared to people who sleep at home. This study aims to determine whether there is an effect of foot massage and progressive muscle relaxation on sleep quality in congestive heart failure (CHF) patients in the CVCU ward of Grandmed Lubuk Pakam Hospital. This research uses a semi-experimental (semi-trial) type of research with a one-group pre-trial study design, the intervention carried out using this method uses two groups. The first group consisted of CHF patients with decreased sleep quality and foot massage. The second group consisted of CHF patients with a gradual decrease in sleep quality and muscle relaxation. Based on the Wilcoxon test above, the test results with p-value are obtained:0.004 means p < 0.05 so it can be concluded that progressive foot and muscle massage has a significant effect on the sleep quality of congestive heart attack (CHF) patients at GrandMed Lubuk Pacam Hospital. It is recommended that patients who experience sleep disorders, especially CHF patients, massage their feet before going to bed.